Analysis of Risk Factors for Major Adverse Cardiovascular Events in Patients with Coronary Stent Restenosis after Revascularization - Zhuoxuan Yang; Tianjie Wang; Ying Dong; Long Liu; Xuan Xue; Jine Wu; Liuyi Hao; Jiansong Yuan; Jingang Cui; Shubin Qiao; Weixian Yang (Reviews in Cardiovascular Medicine, 2023)
Background: To investigate the risk factors for myocardial infarction, recurrent in-stent restenosis (ISR) and target vessel revascularization (TVR) in patients with coronary ISR within 4 years after revascularization. Methods: A total of 1884 patients who were hospitalized at Fuwai Hospital for ISR and successfully treated with coronary intervention between January 2017 and December 2018 were included to determine whether there were myocardial infarction, recurrent ISR, TVR and other major adverse cardiovascular events (MACEs) within 4 years after intervention. The patients were divided into the MACE group (215 patients) and the non-MACE group (1669 patients). The clinical data of patients in the two groups were compared, and the risk factors for postoperative MACEs in the ISR patients were obtained by multivariate logistic regression analysis. The receiver operating characteristic (ROC) curve was used to determine the optimal prediction threshold for postoperative MACEs in ISR patients. The difference in survival curves between the two groups was compared using Kaplan‒Meier survival analysis. Results: The albumin (43.42 ± 4.77 vs. 44.17 ± 4.46, p = 0.021), direct bilirubin (2.5 (2, 3.5) vs. 2.8 (2.07, 3.73), p = 0.036) and free triiodothyronine (FT3) (2.85 ± 0.43 vs. 2.92 ± 0.42, p = 0.019) levels in the MACE group were significantly lower than those in the non-MACE group, and there was a significant negative correlation between albumin and FT3 and MACEs. The results of univariate and multivariate logistic regression analyses revealed that FT3 was an independent predictor of postoperative MACEs in ISR patients (Odds Ratio (OR) = 0.626, 95% CI: 0.429–0.913, p = 0.015). The ROC curve analysis determined that an FT3 value of 2.785 pmol/L was the optimal prediction threshold. According to the threshold, ISR patients were divided into the FT3 <2.785 group and the FT3 ≥2.785 group. The Kaplan‒Meier analysis revealed that the postoperative recurrence rate of MACEs of the FT3 <2.785 group was substantially greater than that of the FT3 ≥2.785 group (Hazard Ratio (HR) = 0.76, 95% CI: 0.58–0.994, p = 0.044). Conclusions: FT3 can be used as an independent predictor of postoperative myocardial infarction, recurrent ISR and TVR in ISR patients. When FT3 is <2.785 pmol/L, the incidence of postoperative myocardial infarction, recurrent ISR and TVR in ISR patients increases significantly.